2009
DOI: 10.1029/2009je003339
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hydrated silicate minerals on Mars using MRO‐CRISM: Geologic context near Nili Fossae and implications for aqueous alteration

Abstract: [1] The Noachian terrain west of the Isidis basin hosts a diverse collection of alteration minerals in rocks comprising varied geomorphic units within a 100,000 km 2 region in and near the Nili Fossae. Prior investigations in this region by the Observatoire pour l'Minéralogie, l'Eau, les Glaces, et l'Activité (OMEGA) instrument on Mars Express revealed large exposures of both mafic minerals and iron magnesium phyllosilicates in stratigraphic context. Expanding on the discoveries of OMEGA, the Compact Reconnais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
739
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 550 publications
(768 citation statements)
references
References 109 publications
27
739
0
2
Order By: Relevance
“…Though we do not match the spectrum in the CRISM image of Claritas rise (FRT0000634B) in Fig. 13 to a particular phyllosilicate, Ehlmann et al (2009a) recently identified it as 'serpentine', along with further identifications of serpentine in the Nili Fossae region (Ehlmann et al, 2009b).…”
Section: Crism Analysis Of the Claritas Rise-forming Rock Materialsmentioning
confidence: 99%
“…Though we do not match the spectrum in the CRISM image of Claritas rise (FRT0000634B) in Fig. 13 to a particular phyllosilicate, Ehlmann et al (2009a) recently identified it as 'serpentine', along with further identifications of serpentine in the Nili Fossae region (Ehlmann et al, 2009b).…”
Section: Crism Analysis Of the Claritas Rise-forming Rock Materialsmentioning
confidence: 99%
“…A northward traverse would cross the boundary between distinct, diverse units exposing Hesperian and Noachian-aged sequences with hydrated and phyllosilicate mineral signatures (Bibring et al, , 2006Ehlmann et al, 2010;Mustard et al, 2008Mustard et al, , 2010Poulet et al, 2007). Many of the mineral signatures may comprise evidence for past habitable environments (Farmer and Des Marais, 1999).…”
Section: Narrowing the List Of Candidate Sitesmentioning
confidence: 99%
“…With these guidelines in mind, seven new candidate sites were submitted by the science community and discussed by the Steering Committee in December 2009 (Tables 4 and 5, Fig. 3): 1) Nili Fossae carbonate plains (Ehlmann et al, 2008b) including ultramafic, phyllosilicate-bearing, and carbonate-bearing outcrops (21.7 N, 78.8E), 2) a diverse assemblage of minerals straddling the Noachian-Hesperian boundary in northeast Syrtis Major (16.71N,76.91E) with an ellipse to the north of the previous Syrtis sites (e.g., Bibring et al, 2005Bibring et al, , 2006Ehlmann et al, 2010;Mustard et al, 2008Mustard et al, , 2010Poulet et al, 2007), 3) a delta deposit Fig. 4.…”
Section: The Third Community Workhop and Beyondmentioning
confidence: 99%
“…Farmer et al, 1996), and potential hydrothermal mineral assemblages identified from orbit (e.g. Ehlmann et al, 2009). Chojnacki & Hynek (2008) attribute some of the widespread Valles Marineris sulfate deposits to high temperature basalt alteration.…”
Section: Background: Mars Hydrothermal Alterationmentioning
confidence: 99%
“…Yen et al, 2008), and through remote sensing from the Mars Reconnaissance Orbiter (MRO, e.g. Ehlmann et al, 2009). …”
Section: Introductionmentioning
confidence: 99%